Longitudinal associations of Internet use with cognitive and social resources among older adults - Toh, Wei Xing (2025)
Objectives: While cognitive and social resources are two commonly studied correlates of Internet use, their directionality with Internet use remains unclear. Therefore, we examined the potential reciprocal associations of cognitive and social resources with Internet use frequency in late adulthood. Method: We analyzed three waves of longitudinal data from the English Longitudinal Study of Ageing (Mage = 67.62 years, SDage = 9.62 years), with biennial follow-ups over 4 years. Using random-intercept cross-lagged panel models, we examined within-person cross-lagged associations involving self-reported Internet use frequency with the general and specific facets of cognitive (i.e., episodic memory and verbal fluency) and social (i.e., contact frequency, network size, and social support) resources. Results: Our within-person findings indicated bidirectional associations between cognitive resources and Internet use, and unidirectional relations between Internet use and social resources. For cognitive resources, general and specific indicators of cognitive functioning at an earlier timepoint were positively linked to subsequent Internet use frequency. In turn, Internet use frequency positively preceded episodic memory, but not verbal fluency. For social resources, prior Internet use frequency was positively associated with the structure (i.e., contact frequency, size of socially close relationships), but not the quality (i.e., social support), of social relationships two years later. Conversely, social resources did not predict Internet use frequency. Conclusion: Our findings shed light on the cognitive and social antecedents and outcomes of Internet use, thereby providing valuable insights for designing interventions that promote Internet adoption and quality of life among older adults.